Pengaruh Partisipasi Anggaran terhadap Kinerja Karyawan dengan Budaya Organisasi dan Kepuasan Kerja Sebagai Variabel Intervening, Bank Rakyat Indonesia Kantor Cabang Bandar Lampung - Tri Utari; Yuliansyah Yuliansyah; Pigo Nauli (Penerbit Goodwood, 2022)
Purpose: The aim of this study is to examine the influence of budget participation to employee performance through organizational culture and work-satisfaction-based. Research methodology: The influence of budget participation on employee performance with organizational culture and job satisfaction as an intervening variable was carried out using descriptive analysis methods, with data collection applications using a questionnaire. Results: Budget participation has a direct effect on employee performance. The higherthe level of employee participation in the budget preparation process, the better the employee's performance. Limitations: The sample of this study was only 80 employees at the Bank Rakyat Indonesia, Bandar Lampung Branch, due to time constraints and the Covid-19 pandemic. Contribution: This research is useful for companies to see whether budget participation affects employee performance.